Peran Kedisiplinan, Etika dan Kepatuhan Kerja: Tinjauan Teoritis dan Literatur - Adhelya, Talitha; Nabila, Nur; Putri, Gita Sephia; Surman, Surman (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to analyze the role of discipline, work ethics, and compliance in shaping employee work behavior through a theoretical approach and literature review. These three aspects are considered fundamental elements that contribute to improving work effectiveness and achieving organizational targets. The research method used is a literature review, examining 11 relevant scientific references, including national and international journals discussing discipline, work ethics, compliance, and employee performance. Research findings indicate that work ethics serve as a moral foundation that influences the development of disciplined behavior and compliance in carrying out tasks. Discipline is closely related to compliance, especially in the implementation of standard operating procedures, adherence to regulations, and fulfillment of work responsibilities. Furthermore, these three variables positively impact the improvement of performance, productivity, organizational commitment, and job satisfaction across various fields. Therefore, this literature review affirms that discipline, work ethics, and compliance are interconnected foundations of work behavior and have a significant influence on organizational effectiveness. The results of this study are expected to serve as a reference for the development of policies, training programs, and human resource management strategies in the workplace.